2021
DOI: 10.1038/s41598-021-96754-1
|View full text |Cite
|
Sign up to set email alerts
|

First tracks of newborn straight-tusked elephants (Palaeoloxodon antiquus)

Abstract: Tracks and trackways of newborns, calves and juveniles attributed to straight-tusked elephants were found in the MIS 5 site (Upper Pleistocene) known as the Matalascañas Trampled Surface (MTS) at Huelva, SW Spain. Evidence of a snapshot of social behaviour, especially parental care, can be determined from the concentration of elephant tracks and trackways, and especially from apparently contemporaneous converging trackways, of small juvenile and larger, presumably young adult female tracks. The size frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The lowermost pedogenic level PS1 28 , located immediately under U1, is characterised by yellowish-reddish mottled colours and an extensive network of polygonal mats of at least 300 m in length, which is the maximum surface area exposed so far (Fig. 7 ) which preserves both hominin fossil footprints 6 and other associated vertebrate tracks 13 15 . Medium-fine sands form PS1 with a silty matrix (sample PS-2/0.3 m) displaying a strong vertically elongated arrangement of mottling, suggesting a genetic relationship with plant-root activity 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowermost pedogenic level PS1 28 , located immediately under U1, is characterised by yellowish-reddish mottled colours and an extensive network of polygonal mats of at least 300 m in length, which is the maximum surface area exposed so far (Fig. 7 ) which preserves both hominin fossil footprints 6 and other associated vertebrate tracks 13 15 . Medium-fine sands form PS1 with a silty matrix (sample PS-2/0.3 m) displaying a strong vertically elongated arrangement of mottling, suggesting a genetic relationship with plant-root activity 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a new track site with hominin footprints 6 and tracks ascribed to the auroch Bos primigenius ?, the red deer Cervus elaphus , the wild boar Sus scrofa , as well as Elephantidae ( Palaeoloxodon antiquus ), Canidae ( Canis lupus ), and waterbirds (geese, Anserinae, and waders, Charadrii) 13 15 was studied in the Asperillo Cliff, close to Matalascañas (Doñana Shoreline, Spain, Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…These sites also included the tracks of elephants, which extended the last appearance date of elephants in this region by 300 thousand years 35 . Many of the other sites reviewed here preserve remarkable records of the mammalian biodiversity surrounding hominins—for example, sites along the Cape south coast document extensive track assemblages of giraffes, crocodiles, and birds, 69 and the track surface at Matalascañas records a wide variety of differently sized and aged elephant tracks 88 …”
Section: What Has This Growing Source Of Data Taught Us About Human E...mentioning
confidence: 99%
“…35 Many of the other sites reviewed here preserve remarkable records of the mammalian biodiversity surrounding hominins-for example, sites along the Cape south coast document extensive track assemblages of giraffes, crocodiles, and birds, 69 and the track surface at Matalascañas records a wide variety of differently sized and aged elephant tracks. 88 In the right depositional contexts, both skeletal fossils and track assemblages can be well-documented within the same geological sequence. Such cases provide opportunities to directly compare the faunal records associated with both types of fossil data and build a more comprehensive picture of local paleoenvironments.…”
Section: Hominin Ecologymentioning
confidence: 99%
“…de Carvalho et al (2021), the estimates of ground support surface for all four feet would be comprised between 0.24 kg/m 2 in calves and 1.03 kg/m 2 in old adults, respectively.In the case of the giant, short-limbed Hippopotamus antiquus(Palmqvist et al, 2022b),Behrensmeyer and Laporte (1981) reported on the nding of single footprints and trails of large vertebrates in a 12 cm thick unit of sandy muds (sand:silt:clay = 12:59:29), dated to 1.6-1.5…”
mentioning
confidence: 99%